RANCANG BANGUN SISTEM INFORMASI SIMPAN PINJAM KARYAWAN MENGGUNAKAN METODE OBJECT ORIENTED PROGRAMMING (STUDI KASUS: PT. ARTA BUANA SAKTI TANGERANG) - Eka W. Fridayanthie; Jimmy Charter (Jurnal Techno Nusa Mandiri, 2016)
Computers provide an appropriate solution to generate information for the needy at this time. Just as happens in any company, either company-owned government and private relatively large transaction that required a database to store and process data efficiently, fast and can be used anytime when needed. PT. Arta Buana Sakti is a company engaged in the property has made a savings and loans to employees where the employee saving and loan was founded in 2014 with the number of members has reached 121 members in March 2016. There are constraints that have progressed saving which this employee to perform reporting pieces mandatory saving and loan installment payments need to see all the membership book and add up all the bills, it takes the computerized system so that transactions go well and quickly implemented at this stage, the authors conducted a saving and loan information system design and design the look of the program employees use integrated development environment (IDE) NetBeans with Java programming language and MySQL as the database